Evaluation of Water Productivity under Furrow Irrigation for Onion (Allium cepa L.) Crop - Ligalem Agegn Asres; Pratap Singh; Melkamu Ateka Derebe; Babur Tesfaye Yersaw (Advances in Agriculture)
Irrigation water management practices are the main strategies to improve water productivity. This research work was focused to study the performance of alternate and paired row furrow irrigation systems at three levels of irrigation (100%, 75%, and 50% of crop evapotranspiration) using different water productivity indicators for onion crops. The experiment had six treatments and replicated three times to evaluate the analysis of variance in SAS software. Water productivity indicators like crop water use efficiency, field water use efficiency, and field water expense efficiency were determined through bulb yield and water which were used by the crop. The crop yield was expressed as the total yield of onion bulbs, and crop water use was expressed as crop evapotranspiration (ETc), gross depth of irrigation, and water expense. The estimated maximum values of crop water use efficiency, field water use efficiency, and field water expense efficiency were 11.941, 16.152, and 9.361 kg m−3, respectively, for paired row furrow irrigation with 50% ETc. The performance of the paired row furrow irrigation system in crop yield and water use was better as compared to the alternate furrow irrigation system at all levels of irrigation.